Aluminum-substituted phosphotungstic acid/sulfonated poly ether ether ketone nanocomposite membrane with reduced leaching and improved proton conductivity. (November 2016) - Banerjee, Soma; Kar, Kamal K
Aluminum-substituted tungstophosphoric acid (AlTPA)/sulfonated poly ether ether ketone (SPEEK) (sulfonation degree approximately 77%) nanocomposite membranes have been prepared for fuel cell application. AlTPA nanoparticles are synthesized by the reaction of TPA and aluminum nitrate in aqueous medium. X-ray diffraction, energy dispersive X-ray, Fourier transform infrared and Raman spectroscopies, and field-emission scanning electron microscopy (FESEM) are used to characterize the AlTPA particles and SPEEK. Study reveals that 2.31 numbers of protons of TPA have been replaced by Al 3+ in AlTPA with retention of Keggin's structure. Nanocomposite membranes with varying AlTPA and TPA content are prepared and evaluated by measuring water uptake, ion exchange capacity, equilibrium water content, water desorption rate, proton conductivity, leaching tendency, and thermal properties. SPEEK/AlTPA nanocomposite membrane exhibits proton conductivity as high as 1.09 mS cm −1 at 10 wt% filler loading. Leaching of filler is reduced by approximately 92% in SPEEK/AlTPA nanocomposite membrane compared to SPEEK/TPA membrane. SPEEK/AlTPA membrane shows approximately 15% higher equilibrium water content and approximately 57% reduction in water desorption rate as compared to SPEEK/TPA membrane. Membranes are thermally stable up to 215°C, which is well above the operating temperature of fuel cells. Composite films are also examined by FESEM to gain further insights into the microstructure.